The Ste20 Family Kinases MAP4K4, MINK1, and TNIK Converge to Regulate Stress-Induced JNK Signaling in Neurons - Larhammar, Martin (J Neurosci, 2017)
The c-Jun-N-terminal kinase (JNK) signaling pathway regulates nervous system development, axon regeneration, and neuronal degeneration after acute injury or in chronic neurodegenerative disease. Dual leucine zipper kinase (DLK) is required for stress-induced JNK signaling in neurons, yet the factors that initiate DLK/JNK pathway activity remain poorly defined. In the present study, we identify the Ste20 kinases MAP4K4, misshapen-like kinase 1 (MINK1 or MAP4K6) and TNIK Traf2- and Nck-interacting kinase (TNIK or MAP4K7), as upstream regulators of DLK/JNK signaling in neurons. Using a trophic factor withdrawal-based model of neurodegeneration in both male and female embryonic mouse dorsal root ganglion neurons, we show that MAP4K4, MINK1, and TNIK act redundantly to regulate DLK activation and downstream JNK-dependent phosphorylation of c-Jun in response to stress. Targeting MAP4K4, MINK1, and TNIK, but not any of these kinases individually, is sufficient to protect neurons potently from degeneration. Pharmacological inhibition of MAP4Ks blocks stabilization and phosphorylation of DLK within axons and subsequent retrograde translocation of the JNK signaling complex to the nucleus. These results position MAP4Ks as important regulators of the DLK/JNK signaling pathway. SIGNIFICANCE STATEMENT Neuronal degeneration occurs in disparate circumstances: during development to refine neuronal connections, after injury to clear damaged neurons, or pathologically during disease. The dual leucine zipper kinase (DLK)/c-Jun-N-terminal kinase (JNK) pathway represents a conserved regulator of neuronal injury signaling that drives both neurodegeneration and axon regeneration, yet little is known about the factors that initiate DLK activity. Here, we uncover a novel role for a subfamily of MAP4 kinases consisting of MAP4K4, Traf2- and Nck-interacting kinase (TNIK or MAP4K7), and misshapen-like kinase 1 (MINK1 or MAP4K6) in regulating DLK/JNK signaling in neurons. Inhibition of these MAP4Ks blocks stress-induced retrograde JNK signaling and protects from neurodegeneration, suggesting that these kinases may represent attractive therapeutic targets.